Waste management through life cycle assessment of products; IOP Conference Series: Materials Science and Engineering; Vol. 81 : Radiation-Thermal Effects and Processes in Inorganic Materials - Borodin Yu. V. Yuri Viktorovich (2015, 2015)
Title screen